Pengaruh Budaya Organisasi Syariah Terhadap Kinerja Karyawan: Studi pada Yayasan Pengembangan Pendidikan Dinamika (YPPD) Cikarang - Saga Cindai Alisanda; Samukri; Hasanah (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the influence of Sharia organizational culture on employee performance within a work environment that upholds Islamic values. The Sharia organizational culture includes principles such as discipline, work motivation, and compensation based on Islamic teachings, specifically in relation to the performance of employees at the Dinamika Education Development Foundation (YPPD) Cikarang. This study employs a quantitative research approach by distributing questionnaires to employees. A saturated sampling method was used, involving all 101 employees as respondents. The data were analyzed using path analysis to examine the relationship between Sharia organizational culture and employee performance. The results of the analysis show that: (1) There is a direct positive effect of discipline on employee performance at YPPD Cikarang, (2) There is a direct positive effect of work motivation on employee performance at YPPD Cikarang, (3)There is a direct positive effect of compensation on employee performance at YPPD Cikarang. These findings indicate that elements supporting a strong organizational cultur, such as discipline, motivation, and compensation play a significant role in enhancing performance, in alignment with Sharia ethical principles within the workplace.